Role of selenium in the pathogenesis of insulin resistance and diabetes mellitus - E.N. Dudinskaya (LLC "MEDIAFORMAT", 2024)
Insulin resistance (IR) and type 2 diabetes mellitus (T2D) represent serious, steadily progressing global epidemics involving millions of people all over the world. IR is associated with numerous concomitant disorders, including T2D that inevitably complicates the course and outcomes of cardiovascular disorders and represents one of the leading causes of death in the population [1]. It is well known that IR leads to hyperinsulinemia, increase in chronic inflammation and oxidative stress, which finally result in the vascular wall morphofunctional alterations and accelerate atherogenesis and arteriosclerosis. Micronutrients, such as selenium (Se) and zink (Zn) that are involved in antioxidant defense and maintaining reparative properties of the endothelium, play an important role in these processes. Furthermore, selenium regulates the immune function and some glucose metabolism processes, which causes interest in their role in the pathogenesis of IR and T2D. The paper provides the analysis of current data on the impact of selenium on the risk of T2D based on the recent studies.